New Symmetric Enhanced-Boost Modified Z-Source Inverters with Switched Z-Impedance - Subhani, N. (Institute of Electrical and Electronics Engineers Inc., 2020)
In this paper, two new symmetric structures are proposed to modify existing enhanced-boost Z-source inverter (EB-ZSI) by employing the same number of components in the Z-impedance network. The Z-impedance network in the first structure is connected in parallel with H-bridge circuit to form a topology called, enhanced-boost modified Z-source inverter (EBM-ZSI) while the second topology is named as improved EBM-ZSI (iEBM-ZSI) where Z impedance network is connected in series to H-bridge circuit. The proposed structures or topologies exhibit less capacitor voltage stresses on their impedance networks and input start-up inrush current for a similar boost factor and voltage gain to that of an EB-ZSI. The proposed iEBM possesses a common ground feature along with the improved performance in terms of reducing both the capacitor voltage stress and input start-up inrush current as compared to both EBM-ZSI and EB-ZSI. This paper presents some analyses to support these claims and simulation studies are carried out to further strengthen the analytical results. Â© 2020 IEEE.